Urachal abscess in a child with single kidney and multiple anomalous vertebrae-a case report and literature review - Mohamad K. Abou Chaar; Tamador Al-Shamaileh; Mohammad M. Saleem (SpringerOpen, 2020)
Abstract Background Urachal anomalies (UAs) are rare in children; the most encountered are urachal cysts, urachal sinus, and urachal diverticulum. Other associated anomalies have been reported to include renal and abdominal wall defects. No skeletal anomalies have been reported to date. Case presentation We present a case of a 20-month-old female patient, who presented to our emergency department with a fever of 2 weeks duration associated with colicky abdominal pain, a tender abdomen, and an infraumbilical mass. The suspicion of urachal sinus abscess was confirmed by ultrasound. The patient was also found to have a single left kidney and multiple vertebral segmental anomalies on a full-body computed tomography scan. The patient underwent open surgical excision of the urachal abscess without complications on follow-up. Conclusion Urachal abscess is rare in children. Associated anomalies include renal and abdominal wall defects. To our knowledge and based on our meticulous search through the literature, this is the first case to report a combination of renal and skeletal findings in a child. Whenever a urachal remnant is found in a patient, a radiological investigation should be made to rule out associated anomalies.